Metode Tafsir Imām Al-Syāfi’i Dalam Kitab Al-Risālah - Muhammad Esa Prasastia Amnesti; Setio Budi; Abdul Kadir Riyadi; Abdul Rofiq (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Imam al-Syafi'i has a very important role in the development of science in Islam,besides being known as a faqih (fiqh expert), Imam Syafi'i is one of the figures who are very understanding of the meanings of the Qur'an. Therefore, this study aims to find out the thoughts about the method of interpretation in the book al-Risalah. Because basically this book was written as a gift from Abdurahman bin Mahdi regarding the content of the meaning of the Qur'an. Using a qualitative approach (library research), the results show that in the book of al-Risalah, Imam Syafi'i's method of understanding the Qur'an can be found using the sources bil-Ma'tsur or bil-Riwayah, both the Qur'an , hadith, opinions of friends and the words of the tabi'in.